(x+5)^3-3=-67 11-(2x-3)^2=2

Question

(x+5)^3-3=-67
11-(2x-3)^2=2

in progress 0
Helga 1 year 2020-11-27T06:02:14+00:00 2 Answers 60 views 0

Answers ( )

    0
    2020-11-27T06:03:51+00:00

    Đáp án:

    ` (x+5)^3  – 3 = -67`

    ` => (x+5)^3 = -67 + 3 = -64`

    ` => (x+5)^3 = (-4)^3`

    ` => x +5 = -4`

    ` => x= -4 -5  = -9`

    Vậy ` x= -9`

    *****

    ` 11 – (2x-3)^2 = 2`

    ` => (2x-3)^2 = 11- 2  = 9`

    TH1

    ` 2x -3 = 3`

    ` => 2x = 6`

    ` => x= 3`

    TH2

    ` 2x -3 = -3`

    ` => 2x = 0`

    ` => x= 0`

    Vậy ` x= 0` hoặc ` x= 3`

     

    0
    2020-11-27T06:04:02+00:00

    Đáp án:

    Giải thích các bước giải:

     

    5-3-3-67-11-2-3-2-2

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )